Method for preparing high-performance copper-titanium alloy through aerosol jet printing technology
The preparation of copper-titanium alloys through aerosol jet printing technology has solved the problems of contradiction between mechanical and electrical properties of copper-titanium alloys and poor high-temperature stability in the prior art, and achieved efficient and low-cost high-performance copper-titanium alloy preparation.
Patent Information
- Application Number
- CN202510264752.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-07
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-03-07
AI Technical Summary
The existing copper-titanium alloy manufacturing technology has contradictions between mechanical properties and electrical properties, poor high temperature stability, high sintering temperature, large energy consumption, and difficult to take into account both cost and performance.
Aerosol spray printing technology is used to remove impurities and mix with copper salt solution, and reduce the reaction to form a copper-clad titanium powder, and anneale under a mixed atmosphere of hydrogen and argon to prepare a high-performance copper-titanium alloy.
It significantly reduces the sintering temperature, reduces energy consumption, improves the mechanical properties, electrical properties and high temperature stability of copper-titanium alloys, and provides an efficient and low-cost industrial production method.
Smart Images

Figure CN119747678A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of chemical synthesis, and in particular to a method for preparing a high-performance copper-titanium alloy by using an aerosol jet printing technology. Background Art
[0002] Copper, due to its excellent electrical and thermal conductivity, plays a core role in the manufacture of electronic components and industrial components. Among them, copper-titanium alloy, as an outstanding representative of copper-based materials, exhibits superior mechanical properties and is regarded as an ideal alternative to copper-beryllium alloy, with broad market application potential. Traditionally, current-carrying components mostly use copper-beryllium alloys, but in view of the high cost of beryllium and its long-term threat to the environment and human health, it is imperative to develop cost-effective and environmentally friendly alternative materials. Copper-titanium alloy is not only low-cost and has little environmental impact, but if it can effectively combine high electrical conductivity, excellent mechanical properties and high-temperature thermal stability, its application areas will expand from current-carrying components to multiple industries such as defense and aviation manufacturing.
[0003] The solid solution strengthening effect of titanium in copper significantly enhances the strength of the alloy. As the titanium content increases, this strengthening effect becomes more obvious, however, the electrical conductivity decreases. Therefore, in order to take into account both mechanical and electrical properties, the titanium content is usually controlled below 5%. Current research focuses on optimizing the overall performance of copper-titanium alloys by incorporating a variety of trace alloying elements. Although this type of multi-element alloy has improved mechanical properties, the thermal conductivity of the introduced elements is generally lower than that of pure copper, which increases electron scattering and may have an adverse effect on electrical conductivity. The preparation of ternary or multi-element copper-titanium alloys requires precise control of the content of each element and optimization of the final microstructure to reconcile the contradiction between mechanical and electrical properties. This process is complicated, and the resulting materials often show high strength but low elongation, and the overall performance improvement is limited. In addition, although the alloy properties can be improved by deformation aging treatment, oxygen impurities are easily mixed in the process, which increases the cost burden.
[0004] The traditional manufacturing technology of copper-titanium alloys mainly covers three core processes: vacuum induction melting, vacuum arc consumable melting and mixed powder sintering technology.
[0005] Vacuum induction melting technology is characterized by a natural cooling process with a slow cooling rate, which directly leads to an increase in the grain size inside the ingot. The larger grain structure is prone to cracking during the subsequent work hardening of the material, which seriously limits the qualified rate of the finished alloy sheet or ingot. Further mechanical processing steps will further aggravate this loss, making the output efficiency of the final product low.
[0006] The vacuum arc consumable melting technology can produce high-quality ingots with fine structure and uniform composition by precisely controlling the cooling rate of the molten droplets and using electromagnetic stirring to ensure uniform composition, which significantly improves the performance stability and overall yield of the material. However, the limitation of this technology is that the subsequent mechanical processing is difficult, and the high production cost has become an obstacle to its widespread application.
[0007] The mixed powder sintering technology has shown the advantage of high tolerance to raw materials. It achieves powder uniformity through simple physical mixing, and then uses cold isostatic pressing and sintering process to prepare ingots. This method not only ensures the uniformity of the composition, but also achieves high yield and molding efficiency, and the processing flow is simple. However, since the material has not been molten, the degree of grain refinement is limited, resulting in the product usually showing a larger grain size and relatively low mechanical strength.
[0008] The document with application number 201410471560.5 discloses a CuTi-based elastic copper alloy and its preparation method. The process successfully produces a multi-component copper-titanium alloy through smelting, rolling and subsequent heat treatment, and its tensile strength exceeds 1000MPa. However, the elongation of this alloy is only about 5%, indicating that its application ability is limited in high temperature environment.
[0009] The document with application number 201910334755.8 discloses a method for preparing ultrafine-grained copper-titanium alloy wire, which adopts powder metallurgy technology. The product is rich in nano-scale titanium particles, showing excellent hardness, strength and conductivity, and the elongation range is extended to 5% to 8%. However, the preparation procedure is relatively complicated, and the stability of the alloy under high temperature conditions still needs to be further enhanced.
[0010] In view of this, the preparation of copper-titanium alloy powder exposes problems such as insufficient product performance, failure to take into account both mechanical and electrical properties, poor high-temperature stability, high sintering temperature, and high energy consumption. There is an urgent need for a new method with high efficiency, high yield, low cost, and environmental friendliness to meet the needs of industrial production. Summary of the invention
[0011] In view of the deficiencies in the prior art, the technical problem to be solved by the present invention is to provide a method for preparing a high-performance copper-titanium alloy using an aerosol jet printing technology.
[0012] The technical solution of the present invention to solve the technical problem is to provide a method for preparing a high-performance copper-titanium alloy by aerosol jet printing technology, which comprises the following steps: Step 1, removing impurities from the surface of titanium powder to obtain refined titanium powder; Step 2, uniformly mixing the refined titanium powder obtained in step 1 with the copper salt solution to obtain a mixture solution; Step 3, adding the reducing agent solution dropwise to the mixed solution of step 2, and then performing a reduction reaction to precipitate copper on the surface of the titanium powder, thereby copper-plating the surface of the titanium powder, until the surface of the titanium powder is completely covered with copper, to obtain a mother solution; Step 4, atomizing the mother liquid obtained in step 3 to form droplets, and conveying them to an aerosol jet printing device; the droplets are conveyed to the printing nozzle by a carrier gas; the carrier gas, the restraining gas and the droplets together form an aerosol jet which is ejected from the printing nozzle, and the aerosol jet is ejected onto the substrate for aerosol jet printing to obtain copper-clad titanium powder; Step 5: annealing the copper-clad titanium powder obtained in step 4 in a mixed atmosphere of hydrogen and argon to perform a reduction reaction, and obtaining a high-performance copper-titanium alloy after cooling.
[0013] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention forms aerosols through aerosol technology, generates copper-clad titanium powder structure in situ during the flight of the aerosol, prepares micron-level copper-clad titanium, and then converts it into copper-titanium alloy through heat treatment. The method is simple and easy to implement, significantly reduces the sintering temperature, reduces energy consumption, and prepares high-strength copper-titanium alloy while ensuring mechanical and electrical properties. The prepared copper-titanium alloy has uniform texture, takes into account both mechanical and electrical properties, and improves high-temperature stability, providing a new route for the industrial production of copper-titanium alloys.
[0014] (2) The present invention uses aerosol technology to prepare micron-sized copper-clad titanium, which has uniform particles, controllable size and high performance. It greatly reduces the temperature during heat treatment and solves the disadvantage of low high-temperature stability of copper-titanium alloy.
[0015] (3) The aerosol particles produced by aerosol technology are small in size, which significantly increases the specific surface area and has a large surface energy, which reduces the activation energy during high-temperature reactions, thereby greatly reducing the temperature during annealing reduction.
[0016] (4) The introduction of aerosol technology in the preparation of copper-titanium alloys changes the element distribution in the alloy, making it more orderly. This greatly improves the high-temperature stability of the copper-titanium alloy and increases its service life, thereby increasing the usage scenarios and expanding the market potential of the copper-titanium alloy.
[0017] (5) The present invention controls the size of the aerosol by adjusting the flow rates of the carrier gas and the confining gas in the aerosol technology, thereby regulating the size and microscopic morphology of the copper-titanium alloy prepared by this method. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a SEM image of the copper-clad titanium powder prepared in Example 1 of the present invention; Figure 2 This is a SEM image of the copper-titanium alloy prepared in Example 1 of the present invention; Figure 3 This is a SEM image of the copper-clad titanium powder prepared in Example 3 of the present invention; Figure 4 This is the XRD pattern of the copper-titanium alloy prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0019] The specific embodiments of the present invention are given below. The specific embodiments are only used to further illustrate the present invention in detail and do not limit the protection scope of the present invention.
[0020] The present invention provides a method for preparing a high-performance copper-titanium alloy by using an aerosol jet printing technology (hereinafter referred to as the method), the method comprising the following steps: Step 1, removing impurities from the surface of titanium powder to obtain refined titanium powder; Preferably, step 1 specifically comprises: adding titanium powder to alkaline solution for ultrasonic stirring and then centrifugal separation, adding titanium powder to an organic solvent for ultrasonic stirring and then centrifugal separation, adding titanium powder to anhydrous ethanol for ultrasonic stirring and then centrifugal separation, removing inorganic and organic impurities on the surface of titanium powder to obtain refined titanium powder.
[0021] Preferably, in step 1, the concentration of the alkali solution is 0.5 mol / L to 3 mol / L (preferably 1.5 mol / L).
[0022] Preferably, in step 1, the alkali solution is one of sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution or sodium phosphate solution (preferably sodium hydroxide solution).
[0023] Preferably, in step 1, the organic solvent is one of acetone, DMF, NMP or DMSO (preferably acetone).
[0024] Preferably, in step 1, the ultrasonic frequency is 1-2.5 MHz, the stirring speed is 100-5000 r / min, the stirring time is 10-120 min, and the temperature is room temperature.
[0025] Step 2, uniformly mixing the refined titanium powder obtained in step 1 with the copper salt solution to obtain a mixture solution; Preferably, in step 2, in the copper salt solution, the copper salt is one of copper formate, copper sulfate, copper chloride, copper acetate or copper nitrate, and the solvent is water.
[0026] Preferably, in step 2, the mass fraction of the copper salt solution is 10-25wt%; and the ratio of the mass of the refined titanium powder to the volume of the copper salt solution is 1g:100-300ml.
[0027] Preferably, in step 2, the mixing is carried out uniformly by stirring; the stirring process is: a rotation speed of 300-1000 r / min, a time of 5-30 min, and a temperature of room temperature.
[0028] Step 3, adding the reducing agent solution dropwise to the mixed solution of step 2 at room temperature, and then performing a reduction reaction to precipitate copper on the surface of the titanium powder, thereby copper-plating the surface of the titanium powder, until the surface of the titanium powder is completely covered with copper, to obtain a mother solution; Preferably, in step 3, the dropping speed is 10-200 ml / min and the temperature is room temperature.
[0029] Preferably, in step 3, the concentration of the reducing agent solution is 0.5-5 mol / L (preferably 2 mol / L); the volume ratio of the reducing agent solution to the mixture solution is 1-2:1-5 (preferably 1:3).
[0030] Preferably, in step 3, in the reducing agent solution, the reducing agent is ascorbic acid, formalin, hydrazine hydrate, glucose or hydroxylamine hydrochloride, and the solvent is water.
[0031] Preferably, in step 3, the reaction time is 2-6 hours and the reaction temperature is 40-80°C.
[0032] Step 4, atomizing the mother liquid obtained in step 3 to form droplets, and conveying them to an aerosol jet printing device through a gas pipe; the droplets are conveyed to a printing nozzle through a carrier gas; the carrier gas, the constrained gas and the droplets together form an aerosol jet and are ejected from the printing nozzle, and the flow rates of the carrier gas and the constrained gas are changed to adjust the width and injection speed of the aerosol jet; the aerosol jet is sprayed onto the substrate, the solvent evaporates to form a gel, the printing height is changed to adjust the solvent evaporation behavior of the aerosol jet in the air, and the printing speed, the number of printing layers and the temperature of the substrate are changed to adjust the oxidation process of the aerosol on the substrate to obtain copper-clad titanium powder; Preferably, in step 4, the atomization process is ultrasonic atomization, and the ultrasonic frequency is 1.5-2.5 MHz.
[0033] Preferably, in step 4, the flow rate of the carrier gas is 200-500 sccm, and the flow rate of the confinement gas is 50-150 sccm.
[0034] Preferably, in step 4, both the carrier gas and the confinement gas are nitrogen or an inert gas, and the inert gas is argon.
[0035] Preferably, in step 4, the printing height is 5-10 mm; the printing speed is 5-50 mm / s, the number of printing layers is 50-500 layers; and the temperature of the substrate is 40-180°C.
[0036] Preferably, in step 4, the substrate is a glass plate.
[0037] Step 5: annealing the copper-clad titanium powder obtained in step 4 in a mixed atmosphere of hydrogen and argon to perform a high-temperature reduction reaction, and obtaining a high-performance copper-titanium alloy after cooling.
[0038] Preferably, in step 5, the reduction reaction temperature is 500-800° C. and the time is 3-10 h.
[0039] Preferably, in step 5, the volume ratio of hydrogen to argon is 1-25:75-99 (preferably 5:95), and the sum of the volume ratios of the two is 100%.
[0040] Embodiment 1: (1) adding titanium powder to a 2 mol / L sodium hydroxide solution at room temperature, ultrasonically stirring and then centrifuging, ultrasonically stirring in acetone and then centrifuging, and ultrasonically stirring in anhydrous ethanol and then centrifuging, with the ultrasonic process being 200 r / min for 15 min to remove inorganic matter, titanium oxide and other organic impurities on the surface of the titanium powder to obtain refined titanium powder; (2) A copper salt solution with a mass fraction of 20% was prepared using copper sulfate at room temperature, 20 g of the above-mentioned refined titanium powder was added to 3 L of the copper salt solution, and the mixture was mixed evenly at a stirring speed of 500 r / min for 10 min to obtain a mixture solution; (3) preparing 1 L of ascorbic acid solution with a concentration of 2 mol / L, and adding it dropwise to the above mixture solution at a rate of 100 ml / min at room temperature, and then reacting it at 40° C. for 2.5 h, so that copper precipitates on the surface of the titanium powder, and the surface of the titanium powder is copper-plated until the surface of the titanium powder is completely covered with copper, thereby obtaining a mother solution; (4) The mother liquid is atomized to form droplets, and the ultrasonic frequency is 1.9 MHz; the droplets are transported to the printing nozzle through a carrier gas, and the carrier gas nitrogen, the constraining gas nitrogen and the droplets together form an aerosol jet. The flow rate of the carrier gas is set to 350 sccm and the flow rate of the constraining gas is set to 85 sccm to control the width and injection speed of the aerosol jet. The aerosol jet is sprayed onto a substrate at 130° C., and the printing height is 5 mm. The solvent evaporation rate of the aerosol jet in the air is controlled, and the printing speed is set to 10 mm / s and the number of printing layers is set to 100 layers to control the oxidation process of the aerosol on the substrate, and finally copper-clad titanium powder is obtained on the substrate; nitrogen is used for both the carrier gas and the constraining gas; (5) The copper-clad titanium powder is annealed in a mixed atmosphere of hydrogen and argon (the volume ratio of hydrogen to argon is 5:95) to perform a reduction reaction at a reduction temperature of 675°C for 6.5 hours. After cooling, a high-performance copper-titanium alloy powder is obtained.
[0041] Depend on Figure 1 It can be seen that the copper-clad titanium powder is successfully coated.
[0042] Depend on Figure 2 It can be seen that the copper-titanium alloy forms a solid solution and the alloy phase is relatively uniform.
[0043] Embodiment 2: (1) adding titanium powder to a 1.5 mol / L sodium hydroxide solution at room temperature, ultrasonically stirring and then centrifuging, ultrasonically stirring in acetone and then centrifuging, and ultrasonically stirring in anhydrous ethanol and then centrifuging, with the ultrasonic process being 200 r / min for 15 min to remove inorganic matter, titanium oxide and other organic impurities on the surface of the titanium powder to obtain refined titanium powder; (2) A copper salt solution with a mass fraction of 13% was prepared using copper acetate at room temperature, 30 g of the above-mentioned refined titanium powder was added to 3 L of the copper salt solution, and the mixture was mixed evenly at a stirring speed of 700 r / min for 20 min to obtain a mixture solution; (3) preparing 1 L of 2 mol / L hydrazine hydrate solution, adding it dropwise to the above mixture solution at a rate of 150 ml / min at room temperature, and then reacting it at 60° C. for 3 h, so that copper precipitates on the surface of the titanium powder, plating the surface of the titanium powder with copper, until the surface of the titanium powder is completely covered with copper, to obtain a mother solution; (4) The mother liquid is atomized to form droplets, and the ultrasonic frequency is 2.1 MHz; the droplets are transported to the printing nozzle through a carrier gas, and the carrier gas nitrogen, the constraining gas nitrogen and the droplets together form an aerosol jet. The flow rate of the carrier gas is set to 275 sccm and the flow rate of the constraining gas is set to 110 sccm to control the width and injection speed of the aerosol jet. The aerosol jet is sprayed onto a substrate at 150°C, and the printing height is 7 mm. The solvent evaporation rate of the aerosol jet in the air is controlled, and the printing speed is set to 20 mm / s and the number of printing layers is 150 layers to control the oxidation process of the aerosol on the substrate, and finally copper-clad titanium powder is obtained on the substrate; nitrogen is used for both the carrier gas and the constraining gas; (5) The copper-clad titanium powder is annealed in a mixed atmosphere of hydrogen and argon (the volume ratio of hydrogen to argon is 5:95) to perform a reduction reaction at a reduction temperature of 750°C for 6 hours. After cooling, a high-performance copper-titanium alloy powder is obtained.
[0044] Embodiment 3: (1) adding titanium powder to a 0.5 mol / L sodium hydroxide solution at room temperature, ultrasonically stirring and then centrifuging, ultrasonically stirring in acetone and then centrifuging, and ultrasonically stirring in anhydrous ethanol and then centrifuging, with the ultrasonic process being 200 r / min for 15 min to remove inorganic matter, titanium oxide and other organic impurities on the surface of the titanium powder to obtain refined titanium powder; (2) A copper salt solution with a mass fraction of 10% was prepared using copper chloride at room temperature, 100 g of the above-mentioned refined titanium powder was added to 1 L of the copper salt solution, and the mixture was mixed evenly at a stirring speed of 1000 r / min for 5 min to obtain a mixture solution; (3) preparing 333 ml of 2 mol / L hydroxylamine hydrochloride solution, adding it dropwise to the above mixture solution at a rate of 50 ml / min at room temperature, and then reacting at 50° C. for 5 h, so that copper precipitates on the surface of the titanium powder, plating the surface of the titanium powder with copper, until the surface of the titanium powder is completely covered with copper, to obtain a mother solution; (4) The mother liquid is atomized to form droplets, and the ultrasonic frequency is 2.5 MHz; the droplets are transported to the printing nozzle through a carrier gas, and the carrier gas nitrogen, the constraining gas nitrogen and the droplets together form an aerosol jet. The flow rate of the carrier gas is set to 500 sccm and the flow rate of the constraining gas is set to 150 sccm to control the width and injection speed of the aerosol jet. The aerosol jet is sprayed onto a 100°C substrate, and the printing height is 6.5 mm. The solvent evaporation rate of the aerosol jet in the air is controlled, and the printing speed is set to 25 mm / s and the number of printing layers is set to 200 layers to control the oxidation process of the aerosol on the substrate, and finally copper-coated titanium powder is obtained on the substrate; nitrogen is used for both the carrier gas and the constraining gas; (5) The copper-clad titanium powder is annealed in a mixed atmosphere of hydrogen and argon (the volume ratio of hydrogen to argon is 5:95) to perform a reduction reaction at a reduction temperature of 800° C. for 4 h. After cooling, a high-performance copper-titanium alloy powder is obtained.
[0045] Depend on Figure 3 It can be seen that the copper-clad titanium powder is well coated and has uniform particle size.
[0046] Depend on Figure 4 It can be seen that the copper-titanium alloy was successfully synthesized.
[0047] Embodiment 4: (1) adding titanium powder to a 3 mol / L sodium hydroxide solution at room temperature, ultrasonically stirring and then centrifuging, ultrasonically stirring in acetone and then centrifuging, and ultrasonically stirring in anhydrous ethanol and then centrifuging, with the ultrasonic process being 200 r / min for 15 min to remove inorganic matter, titanium oxide and other organic impurities on the surface of the titanium powder to obtain refined titanium powder; (2) A copper salt solution with a mass fraction of 16% was prepared using copper formate at room temperature, 30 g of the above-mentioned refined titanium powder was added to 1.5 L of the copper salt solution, and the mixture was mixed evenly at a stirring speed of 300 r / min for 30 min to obtain a mixture solution; (3) preparing 500 ml of a glucose solution with a concentration of 2 mol / L, and adding it dropwise to the above mixture solution at a rate of 75 ml / min at room temperature, and then reacting it at 80° C. for 2 h, so that copper precipitates on the surface of the titanium powder, thereby copper plating the surface of the titanium powder, until the surface of the titanium powder is completely covered with copper, thereby obtaining a mother solution; (4) The mother liquid is atomized to form droplets, and the ultrasonic frequency is 1.7 MHz; the droplets are transported to the printing nozzle through a carrier gas, and the carrier gas nitrogen, the constraining gas nitrogen and the droplets together form an aerosol jet. The flow rate of the carrier gas is set to 425 sccm and the flow rate of the constraining gas is set to 125 sccm to control the width and injection speed of the aerosol jet. The aerosol jet is sprayed onto a substrate at 80°C, and the printing height is 8 mm. The solvent evaporation rate of the aerosol jet in the air is controlled, and the printing speed is set to 45 mm / s and the number of printing layers is set to 300 layers to control the oxidation process of the aerosol on the substrate, and finally copper-clad titanium powder is obtained on the substrate; nitrogen is used for both the carrier gas and the constraining gas; (5) The copper-clad titanium powder is annealed in a mixed atmosphere of hydrogen and argon (the volume ratio of hydrogen to argon is 5:95) to perform a reduction reaction at a reduction temperature of 750°C for 3 hours. After cooling, a high-performance copper-titanium alloy powder is obtained.
[0048] Embodiment 5: (1) adding titanium powder to a 2.5 mol / L sodium hydroxide solution at room temperature, ultrasonically stirring and then centrifuging, ultrasonically stirring in acetone and then centrifuging, and ultrasonically stirring in anhydrous ethanol and then centrifuging, with the ultrasonic process being 200 r / min for 15 min to remove inorganic matter, titanium oxide and other organic impurities on the surface of the titanium powder to obtain refined titanium powder; (2) A copper salt solution with a mass fraction of 25% was prepared using copper nitrate at room temperature, 20 g of the above-mentioned refined titanium powder was added to 4 L of the copper salt solution, and the mixture was mixed evenly at a stirring speed of 900 r / min for 25 min to obtain a mixture solution; (3) preparing 1.33 L of a formalin solution with a concentration of 2 mol / L, and adding it dropwise to the above mixture solution at a rate of 200 ml / min at room temperature, and then reacting it at 70° C. for 6 h, so that copper precipitates on the surface of the titanium powder, thereby copper plating the surface of the titanium powder, until the surface of the titanium powder is completely covered with copper, to obtain a mother solution; (4) The mother liquid is atomized to form droplets, and the ultrasonic frequency is 1.5 MHz; the droplets are transported to the printing nozzle through a carrier gas, and the carrier gas nitrogen, the constraining gas nitrogen and the droplets together form an aerosol jet. The flow rate of the carrier gas is set to 485 sccm and the flow rate of the constraining gas is set to 150 sccm to control the width and injection speed of the aerosol jet. The aerosol jet is sprayed onto a 200°C substrate, and the printing height is 9 mm. The solvent evaporation rate of the aerosol jet in the air is controlled, and the printing speed is set to 50 mm / s and the number of printing layers is set to 500 layers to control the oxidation process of the aerosol on the substrate, and finally copper-clad titanium powder is obtained on the substrate; nitrogen is used as the carrier gas and the constraining gas; (5) The copper-clad titanium powder is annealed in a mixed atmosphere of hydrogen and argon (the volume ratio of hydrogen to argon is 5:95) to perform a reduction reaction at a reduction temperature of 550° C. for 10 h. After cooling, a high-performance copper-titanium alloy powder is obtained.
[0049]
[0050] Any matters not described in the present invention are applicable to the prior art.
Claims
1. A method for preparing high-performance copper-titanium alloy using aerosol jet printing technology, characterized in that: The method comprises the following steps: Step 1, removing impurities from the surface of titanium powder to obtain refined titanium powder; Step 2, uniformly mixing the refined titanium powder obtained in step 1 with the copper salt solution to obtain a mixture solution; Step 3, adding the reducing agent solution dropwise to the mixed solution of step 2, and then performing a reduction reaction to precipitate copper on the surface of the titanium powder, thereby copper-plating the surface of the titanium powder, until the surface of the titanium powder is completely covered with copper, to obtain a mother solution; Step 4, atomizing the mother liquid obtained in step 3 to form droplets, and conveying them to an aerosol jet printing device; the droplets are conveyed to the printing nozzle by a carrier gas; the carrier gas, the restraining gas and the droplets together form an aerosol jet which is ejected from the printing nozzle, and the aerosol jet is ejected onto the substrate for aerosol jet printing to obtain copper-clad titanium powder; Step 5: annealing the copper-clad titanium powder obtained in step 4 in a mixed atmosphere of hydrogen and argon to perform a reduction reaction, and obtaining a high-performance copper-titanium alloy after cooling.
2. The method for preparing high-performance copper-titanium alloy by aerosol jet printing technology according to claim 1, characterized in that: Step 1 specifically comprises: adding titanium powder to alkaline solution for ultrasonic stirring and then centrifugal separation, adding titanium powder to organic solvent for ultrasonic stirring and then centrifugal separation, adding titanium powder to anhydrous ethanol for ultrasonic stirring and then centrifugal separation, removing inorganic and organic impurities on the surface of titanium powder to obtain refined titanium powder.
3. The method for preparing high-performance copper-titanium alloy by aerosol jet printing technology according to claim 2, characterized in that: In step 1, the concentration of the alkali solution is 0.5 mol / L to 3 mol / L; In step 1, the alkali solution is one of sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution or sodium phosphate solution; In step 1, the organic solvent is one of acetone, DMF, NMP or DMSO; In step 1, the ultrasonic frequency is 1-2.5 MHz, the stirring speed is 100-5000 r / min, the stirring time is 10-120 min, and the temperature is room temperature.
4. The method for preparing high-performance copper-titanium alloy by aerosol jet printing technology according to claim 1, characterized in that: In step 2, in the copper salt solution, the copper salt is one of copper formate, copper sulfate, copper chloride, copper acetate or copper nitrate, and the solvent is water; In step 2, the mass fraction of the copper salt solution is 10-25wt%; the ratio of the mass of the refined titanium powder to the volume of the copper salt solution is 1g:100-300ml.
5. The method for preparing high-performance copper-titanium alloy by aerosol jet printing technology according to claim 1, characterized in that: In step 2, the mixing is uniformly carried out by stirring; the stirring process is: the rotation speed is 300-1000 r / min, the time is 5-30 min, and the temperature is room temperature.
6. The method for preparing high-performance copper-titanium alloy by aerosol jet printing technology according to claim 1, characterized in that: In step 3, the concentration of the reducing agent solution is 0.5-5 mol / L; the volume ratio of the reducing agent solution to the mixture solution is 1-2:1-5; In step 3, in the reducing agent solution, the reducing agent is ascorbic acid, formalin, hydrazine hydrate, glucose or hydroxylamine hydrochloride, and the solvent is water.
7. The method for preparing high-performance copper-titanium alloy by aerosol jet printing technology according to claim 1, characterized in that: In step 3, the dropping speed is 10-200 ml / min; In step 3, the reaction time is 2 to 6 hours, and the reaction temperature is 40 to 80°C.
8. The method for preparing high-performance copper-titanium alloy by aerosol jet printing technology according to claim 1, characterized in that: In step 4, the atomization process is ultrasonic atomization, and the ultrasonic frequency is 1.5-2.5 MHz; In step 4, the flow rates of the carrier gas and the confinement gas are changed to adjust the width and injection speed of the aerosol jet; the flow rate of the carrier gas is 200-500 sccm, and the flow rate of the confinement gas is 50-150 sccm; In step 4, the printing height is changed to regulate the solvent evaporation behavior of the aerosol jet in the air; Printing height is 5~10mm; In step 4, the printing speed, the number of printing layers and the temperature of the substrate are changed to control the oxidation process of the aerosol on the substrate; The printing speed is 5~50mm / s, the number of printing layers is 50~500 layers; the temperature of the substrate is 40~180℃.
9. The method for preparing high-performance copper-titanium alloy by aerosol jet printing technology according to claim 1, characterized in that: In step 4, both the carrier gas and the confinement gas are nitrogen or an inert gas, and the inert gas is argon.
10. The method for preparing high-performance copper-titanium alloy by aerosol jet printing technology according to claim 1, characterized in that: In step 5, the reduction reaction temperature is 500-800°C and the time is 3-10h; In step 5, the volume ratio of hydrogen to argon is 1-25:75-99, and the sum of the volume ratios of the two is 100%.
Citation Information
Patent Citations
CuTi-series elastic copper alloy and preparation method thereof
CN104278171A
Preparation method of ultra-fine grain copper-titanium alloy wire
CN110042270A
Preparation method of TiB2 / Cu material
CN107675011A
Carbon-supported ordered platinum-cobalt-copper catalyst for fuel cell and preparation method of catalyst
CN109873176A
Aerosol jet printing method and system for volatile ink
CN110733178A
Cited By
Method for preparing nanoscale neodymium iron boron permanent magnet material by aerosol jet printing technology
CN119920614A